Knowledge, Attitude, and Practice towards COVID-19 among Mothers in Dessie Town, Northeast Ethiopia, 2020 - Debrnesh Goshiye; Zinet Abegaz; Sisay Gedamu (Interdisciplinary Perspectives on Infectious Diseases)
Background. Coronavirus disease 2019 (COVID-19) is a highly infectious disease causing a catastrophic effect, and many of us are worried to find a new normal. Many burdens are occurring in households, predominantly to women and mothers. Women worldwide are naive on COVID-19 symptoms, transmission, and prevention measures and worried on being exposed to coronavirus. The study aimed to assess the mother’s knowledge, attitude, and practice towards COVID-19. Methods. A community-based cross-sectional study was conducted from July 22 to August 7, 2020, in Dessie town, Ethiopia. A total of 634 mothers were included in the study. Multistage cluster sampling was used to take the proper sample. An interviewer-administered pretested structured questionnaire was used. Data were entered into EpiData, version 3.1, and analyzed by using SPSS, version 23. Both binary and multivariate logistic regression analyses were performed to find factors associated with dependent variables. The mean score was used to grade the knowledge, attitude, and practice towards COVID-19. Result. A total of 610 mothers participated in this study, making that a 96.2% response rate. More than half of the respondents 319 (50.3%) were in the age of 28–38 years. About 438 (71.8%) attended grades 1–12. About 531 (87.5%) were married, and most respondents 399 (65.4%) were housewives. The mean scores of knowledge, attitude, and practice were 15.36 (SD = 3.059), 6.4 (1.779), and 7.38 (3.068), respectively. Moreover, about 442 (72.5%), 354 (58%), and 338 (55.4%) of the respondents had good knowledge, a favorable attitude, and good practice on COVID-19, respectively. Conclusion. Almost three-fourths of the mothers had good knowledge of COVID-19. However, more than two-fifths of the participants had an unfavorable attitude and poor practice on COVID-19 preventive measures, which may put a high risk of infection that could worsen maternal morbidity and mortality during this pandemic. Therefore, health education programs for mobilizing and improving COVID-19-related knowledge, attitude, and practice are urgently needed, especially for those mothers who have low access to information due to home duty.